2018
DOI: 10.3389/fmicb.2018.02528
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity and the Geochemical Landscape in the Southwestern Gulf of Mexico

Abstract: Marine sediments are an example of one of the most complex microbial habitats. These bacterial communities play an important role in several biogeochemical cycles in the marine ecosystem. In particular, the Gulf of Mexico has a ubiquitous concentration of hydrocarbons in its sediments, representing a very interesting niche to explore. Additionally, the Mexican government has opened its oil industry, offering several exploration and production blocks in shallow and deep water in the southwestern Gulf of Mexico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 94 publications
6
41
1
Order By: Relevance
“…The Gulf of Mexico has been continuously exposed to hydrocarbons due to the presence of natural oil seeps, and discharges from anthropogenic activities such as extraction and transport of petroleum (MacDonald et al, 2015). Recently, we reported the bacterial diversity from different sediments in the swGoM, and identified several specialized hydrocarbon-degrading genera at a basal level, whose population size could potentially increase during an oil spill (Godoy-Lozano et al, 2018). We thus became interested in the isolation of bacterial consortia and species indigenous to the swGoM, to study their metabolic capabilities in hydrocarbon degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gulf of Mexico has been continuously exposed to hydrocarbons due to the presence of natural oil seeps, and discharges from anthropogenic activities such as extraction and transport of petroleum (MacDonald et al, 2015). Recently, we reported the bacterial diversity from different sediments in the swGoM, and identified several specialized hydrocarbon-degrading genera at a basal level, whose population size could potentially increase during an oil spill (Godoy-Lozano et al, 2018). We thus became interested in the isolation of bacterial consortia and species indigenous to the swGoM, to study their metabolic capabilities in hydrocarbon degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Several species from the genera Pseudomonas, Alcanivorax, Acinetobacter, Marinobacter, Bacillus, Dietzia, Rhodococcus, among others, have been reported as able to degrade aromatic and/or aliphatic hydrocarbons (Wentzel et al, 2007;Ghosal et al, 2016). Usually, marine environments hold hydrocarbon-degrading bacteria in low abundance (Godoy-Lozano et al, 2018), but oil spills trigger blooms of such populations, exhibiting a bacterial succession according to the type of hydrocarbons present. For instance, in the Deepwater Horizon (DWH) spill that occurred in the northern Gulf of Mexico in 2010, Oceanospirillales and Pseudomonas taxa dominated the microbial community when the concentration of n-alkanes and cycloalkanes was highest at depth (900-1300 m) during the initial phase of the spill.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical data obtained in our study were compared to those of water with different origins and from environments with different characteristics to determine which water the T1 and T2 waters most resemble. Such environments were that of drinking water [39], the interior transition zone of the ocean [41], the Red Sea [42], southwest part of the Gulf of Mexico [43], a hot water spring in Siloam, South Africa [44], an integrated system of anaerobic-aerobic reactors for the treatment of wastewater (WW) in Ethiopia [45] and the Yeongsan River Basin of South Korea [46]. The two tanks do not significantly differ in chlorine level, but these levels are statistically higher than those found for seawater and potable water (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our results provide one of the first accounts of the microbiota from free living fishes in Mexico. Some studies have reported on microbiological conditions of the Gulf of Mexico (Godoy-Lozano et al 2018) and of river waters in Mexico (Arellano-Ríos and Rivera-Pahua 2011, Barrera-Escorcia et al 2013), or have analyzed fish destined for consumption in urban markets (Constantino-Casas et al 1997) but no reports exist on the microbiology of fishes utilized in subsistence fisheries, especially related to natural protected areas.…”
Section: Discussionmentioning
confidence: 99%